2017
DOI: 10.1038/ncomms14019
|View full text |Cite
|
Sign up to set email alerts
|

[Au]/[Ag]-catalysed expedient synthesis of branched heneicosafuranosyl arabinogalactan motif of Mycobacterium tuberculosis cell wall

Abstract: Emergence of multidrug-resistant and extreme-drug-resistant strains of Mycobacterium tuberculosis (MTb) can cause serious socioeconomic burdens. Arabinogalactan present on the cellular envelope of MTb is unique and is required for its survival; access to arabinogalactan is essential for understanding the biosynthetic machinery that assembles it. Isolation from Nature is a herculean task and, as a result, chemical synthesis is the most sought after technique. Here we report a convergent synthesis of branched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The glycosidation between diol 8 and acceptor 32 was performed affording an inseparable mixture of pentasaccharides 35 . Earlier reports on the synthesis of pentasaccharide motifs indicated that the diastereomeric ratio would likely result from the C‐5 position of the aglycon due to its inherently more reactive nature compared with the C‐3‐OH . Temperature controlled glycosidations and reversing the addition sequence of glycosyl donor and acceptor did not improve the diastereoselectivity and, more frustratingly, the isomers could not be separated.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The glycosidation between diol 8 and acceptor 32 was performed affording an inseparable mixture of pentasaccharides 35 . Earlier reports on the synthesis of pentasaccharide motifs indicated that the diastereomeric ratio would likely result from the C‐5 position of the aglycon due to its inherently more reactive nature compared with the C‐3‐OH . Temperature controlled glycosidations and reversing the addition sequence of glycosyl donor and acceptor did not improve the diastereoselectivity and, more frustratingly, the isomers could not be separated.…”
Section: Resultsmentioning
confidence: 87%
“…Now,t he stage was set for the gold/silver-catalysed glycosidation in a{ 2 2 + 1} fashion.T he glycosidation between diol 8 and acceptor 32 was performed affording an inseparable mixture of pentasaccharides 35.E arlier reports on the synthesis of pentasaccharidem otifs indicated that the diastereomericr atio would likely result from the C-5 position of the aglycon due to its inherently more reactive nature compared with the C-3-OH. [18,[21][22][23] Temperature controlled glycosidations and reversing the addition sequence of glycosyl donor and acceptor did not improvet he diastereoselectivity and, more frustratingly, the isomersc ould not be separated. Hence, sequential addition of the disaccharide was investigated and installation at the C-5 positionp rior to the C-3 positionw ould be beneficial because the mixtureo fc ompounds, if any,w as expected to be easy to purify.W ith this idea, orthoester 33 was saponified, monosilylated using 1.1 equivalent of TBDPS-Cl at 0 8Ca nd installation of the levulinoate protectionw as carried-out at the C-3 position to afford 36 in 61 %o ver three steps.…”
Section: Synthesis Of Pentaarabinofuranosyl Donormentioning
confidence: 95%
See 1 more Smart Citation
“…The regio‐ and stereochemical issues are major challenges during glycans synthesis, and results in a time‐consuming and tedious process for carbohydrate synthesis . Indeed, examples of the synthesis of long, branched, and complex carbohydrate chains with over 15 units are still limited . Therefore, development of efficient strategies for the assembly of long, branched, and complex carbohydrate sequences is direly needed and remains one of the most challenging tasks for synthetic chemists.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of arabinan oligosaccharides has received considerable attention due to their immense significance in disease management. Several groups have attempted the synthesis of arabinan motifs; a large oligoarabinan with 22 Ara f units,, a henicosasaccharide fragment of AG, and a much larger fragment with 92 saccharide residues have been reported (Figure ).…”
Section: Introductionmentioning
confidence: 99%